2021
DOI: 10.1037/fam0000833
|View full text |Cite
|
Sign up to set email alerts
|

Parenting programs to improve sibling interactions: A meta-analysis.

Abstract: Sibling relationships have a profound and lasting impact on children's development and parents often seek for ways to optimize them. Programs to guide parents in efforts to improve sibling interactions draw from different perspectives (mainly behavior management and mediation) and advise the use of different techniques (mainly direct children's behavior using reinforcement practices or maintain impartiality and facilitate communication). We systematically searched PsycINFO and MEDLINE for randomized evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Concerning the long‐term effects on adult sibling relationships, intersibling violence itself, without exposure to parental violence, may undermine the emotional aspects of adult sibling relationships (i.e., perceived closeness, similarity in values). Plausible alternative explanations, such as intensive sibling rivalry or parental favoritism (Feinberg et al, 2012; Gilligan et al, 2020; Leijten et al, 2021) may account for intersibling violence independent of other family violence and its long‐term negative impact on emotional aspects of sibling relationships. This explanation, however, warrants further research.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the long‐term effects on adult sibling relationships, intersibling violence itself, without exposure to parental violence, may undermine the emotional aspects of adult sibling relationships (i.e., perceived closeness, similarity in values). Plausible alternative explanations, such as intensive sibling rivalry or parental favoritism (Feinberg et al, 2012; Gilligan et al, 2020; Leijten et al, 2021) may account for intersibling violence independent of other family violence and its long‐term negative impact on emotional aspects of sibling relationships. This explanation, however, warrants further research.…”
Section: Discussionmentioning
confidence: 99%
“…The older, more dominant sibling's inertia, both at the positive and negative ends of constructiveness, may be a way to push‐back to the younger sibling and may function to curb processes of escalation. Of course, in everyday life, particularly when children are in the preschool period, there are multiple examples of negative feedback loops: parental interventions, one sibling exiting the interaction (Campione‐Barr, 2017; Leijten et al, 2021; Siddiqui & Ross, 2004) and so on.…”
Section: Discussionmentioning
confidence: 99%
“…By helping children to be slightly more generous in an appraisal of their sibling's actions, parents may be able to shift the directionality of the cascade. A recent meta-analysis of the effects of behavioral versus appraisal/problem solving interventions by parents found that both were effective in improving sibling interaction (Leijten et al, 2021).…”
Section: Mechanisms Of Sibling Influence and The Development Of The R...mentioning
confidence: 99%
See 1 more Smart Citation
“…For those families where sibling caregiving fits within their ethno‐cultural beliefs and practices (Klassen et al, 2020) or where it is a common facet of family functioning (Kiraly et al, 2020; Wikle et al, 2018), a better understanding of the role of sibling warmth may be particularly useful, as past work has shown that mothers did not discourage caregiving when siblings did not get along in families with preschool‐aged children (Morrongiello et al, 2007). Anticipatory guidance and family education materials targeting sibling caregiving during the school‐aged years should incorporate elements of existing programs designed to enhance the quality of sibling relationships (Leijten et al, 2021) into those designed to enhance home safety (Kendrick et al, 2013). These materials must also take into account family characteristics such as age, gender, number of siblings and income level (Damashek et al, 2021) as well as cultural norms and expectations (Zukow‐Goldring, 2002).…”
Section: Discussionmentioning
confidence: 99%